2017
DOI: 10.1080/19476337.2016.1266033
|View full text |Cite
|
Sign up to set email alerts
|

Hen egg carotenoids (lutein and zeaxanthin) and nutritional impacts on human health: a review

Abstract: Hen egg is a unique and important carrier of lipid soluble bioactive carotenoids -lutein and zeaxanthin. Egg yolk carotenoid profile is largely dependent on hen's feed composition. Naturally, lutein and zeaxanthin are polar carotenoids primarily deposited in human retina and provide several protective functions, i.e. protect the macula from damage by blue light, improve visual acuity, and scavenge harmful reactive oxygen species. They have also been linked with reduced risk of agerelated macular degeneration a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 144 publications
(194 reference statements)
1
44
0
Order By: Relevance
“…These carotenoids have been linked to a reduced risk of age-related diseases of the eye, cardiovascular diseases, Alzheimer's, and, possibly, some cancers. Functional foods, beyond basic nutrition, provide micronutrients with many beneficial health effects for human 9 .…”
Section: Results and Discussion Proximate Composition And Total Carotmentioning
confidence: 99%
See 1 more Smart Citation
“…These carotenoids have been linked to a reduced risk of age-related diseases of the eye, cardiovascular diseases, Alzheimer's, and, possibly, some cancers. Functional foods, beyond basic nutrition, provide micronutrients with many beneficial health effects for human 9 .…”
Section: Results and Discussion Proximate Composition And Total Carotmentioning
confidence: 99%
“…Moreover, egg yolk is rich in carotenoids, important pigments that affect consumers' acceptance, with a reddish color varying according to chickens' feed 6 . Carotenoids present many functional properties in health promotion and disease prevention in humans 9 . ω 3 polyunsaturated fatty acids are also relevant nutrients in egg yolks and considered essential fatty acids.…”
Section: Introductionmentioning
confidence: 99%
“…Zeaxanthin is a xanthophyll commonly found in corn, egg yolk, oranges, yellow fruits, flowers and vegetables. It imparts a yellow colour to skin and egg yolk of birds and skin colouration to swine and fish (Tibbetts 2018;Zaheer 2017) and is a well-known prophylactic agent that has been reported to exert preventive action against age-related macular degeneration and cancer (Hirahatake et al 2019). Other application includes its use as food/ feed additive and colourant (E161h) in cosmetics and food industries approved by the European Union (EU).…”
Section: Introductionmentioning
confidence: 99%
“…There are synthetic and natural sources for feed carotenoids (Grashorn & Steinberg, 2002;Beardsworth, 2004). However, there are limitations in the use of synthetic carotenoids, which differ among countries (Grashorn & Steinberg, 2002;Roberts, 2004;Zaheer, 2017;Spasevski et al, 2018). Naturally carotenoid-rich sources are yellow corn, corn gluten meal, alfalfa meal, marigold, algae and red pepper (Leeson & Summer, 1997;Kirkpinar & Erkek, 1999a;Gálvez et al, 2008;Kermanshahi et al, 2011;Zaheer, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These colouring agents form egg yolk colours from golden-yellow to orange (Kirkpinar & Erkek, 1999b). However, it was reported that the hens in organic systems and village-type production systems obtained the colouring agents they needed from green leafy vegetation, insects and excrement while grazing on pasture during the day (Kirkpinar & Erkek, 1999a;Zaheer, 2017). This advantage does not exist in the conventional systems, which constitute the overwhelming majority of poultry production systems.…”
Section: Introductionmentioning
confidence: 99%